Effects of crop rotation and field management methods on weed density and species composition in the southeastern part of Latvia (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Integrated weed management (IWM) is a complex approach to weed control that is based on use of several different methods complementing each other, instead of relying on one single method, like chemical weed control. Weed control methods that can be used as parts of IWM strategy include mechanical weed control, application of herbicides, low tillage, changes in the rate and application time of fertilizers, use of undersown crops and crop rotation. Weed surveys were carried out in 2013 and 2014 in the southeastern part of Latvia. The aim of this study was to assess the effect of crop rotation and other field management practices on weed density and weed species composition using the data collected in the surveys. Survey was carried out in the arable fields of conventional farms within four different size categories. One of the significant factors that explained the variation of weed composition within a field was a proportion of cereals in crop rotation within a four year period. Further surveys are required to estimate the effects of climatic variables. Density-dependence can also be important for practical management decisions for particular weed species and should be investigated.